STRATEGI LOBI DAN NEGOSIASI DALAM MEMBINA HUBUNGAN BAIK KLIEN KSP CITRA ABADI - Yana Ramadhani; Leonard Adrie Manafe (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
This study aims to find out more about lobbying and negotiation strategies in fostering good relations with clients at Koperasi Simpan Pinjam Citra Abadi (CA). This study uses descriptive qualitative analysis, using non-participant observation methods. Data collection was obtained by conducting field observations and interviews as well as data from various information sources. The results obtained prove that CA is successful in lobbying and negotiating with clients in order to obtain the necessary information. Before negotiating, the CA first makes observations relating to the client as an initial plan, develops a negotiation strategy, self-introductions, discusses proposals until the negotiations reach a mutual agreement as evidenced by the cooperation signing. The lobbying and negotiation strategies carried out make the messages and suggestions conveyed by the CA therefore they could be well received and in line with the needs desired by the client. CA also applies a win-win solution negotiation strategy in overcoming problems therefore decisions or mutual agreements with clients could be realized and no party feels disadvantaged.